Analisis Hambatan Belajar Siswa Pada Mata Pelajaran Informatika di MTsN 6 Agam - Herlina, Novia; Sesmiarni, Zulfani; Zakir, Supratman; Ilmi, Darul (Yayasan Lembaga Studi Makwa, 2023)
This research is motivated by students experiencing learning obstacles (learning obstacle) on internet material and computer networks. Students do not practice directly related to the material due to inadequate internet facilities and school regulations that prohibit students to access the internet. Less support for the allocation of time provided for informatics subjects. Students stuttering technology even though they can already use mobile phones for social media and play games. Students who are not equipped with LKPD or modules and learning only focus on notes given by the teacher. Not all students focus on paying attention to the delivery of material by the teacher, so that it results in the lack of understanding of students which causes low learning outcomes. Some students who are less interested in learning informatics feel bored when learning and make noise like talking to friends. Lack of student confidence in asking questions or expressing opinions. With this research, student learning obstacles can be seen in informatics and can be overcome properly, of course it can improve the quality of student learning. The research method used in this study is a quantitative descriptive method aimed at describing the phenomena as it is. Data collection techniques using questionnaires distributed to respondents. The research instrument used was a questionnaire/questionnaire compiled using a Likert scale that serves to provide information related to the answers from respondents in order to collect data about the analysis of student learning barriers in informatics in MTsN 6 Agam. The results of this study in the form of descriptive data analysis showed that n or the amount of data valid variable amounted to 65, with a minium value of 14.00 and the maximum value of 46.00, which was known to the average value of 36.55, and the standard deviation value was 5,534, which means value the average is greater than the standard value so that the data deviation is low. Abstrak Penelitian ini dilatar belakangi oleh Siswa mengalami hambatan belajar (learning obstacle) pada materi internet dan jaringan komputer. Siswa tidak melakukan praktek langsung terkait materi dikarenakan fasilitas internet yang kurang memadai dan peraturan sekolah yang melarang siswa mengakses internet. Kurang mendukungnya alokasi waktu yang disediakan untuk mata pelajaran informatika. Siswa gagap akan teknologi padahal sudah bisa menggunakan handphone untuk media sosial dan bermain games. Siswa yang tidak dibekali dengan LKPD atau modul dan pembelajaran hanya fokus pada catatan yang diberikan guru. Tidak semua siswa fokus memperhatikan penyampaian materi oleh guru, sehingga berakibat ketidakpahaman siswa yang menyebabkan hasil belajar yang rendah. Beberapa siswa yang kurang tertarik pada pembelajaran informatika merasa bosan saat belajar dan membuat kegaduhan seperti berbicara dengan teman. Kurangnya kepercayaan diri siswa dalam mengajukan pertanyaan atau menyampaikan pendapat. Dengan penelitian ini dapat diketahui hambatan belajar siswa pada mata pelajaran informatika dan bisa ditanggulangi dengan baik, tentu dapat meningkatkan kualitas belajar siswa. Metode penelitian yang digunakan dalam penelitian ini adalah metode deskriptif kuantitatif yang ditujukan untuk menggambarkan fenomena-fenomena dengan apa adanya. Teknik pengumpulan data menggunakan kuesioner yang dibagikan kepada responden. Instrumen penelitian yang dipakai adalah angket/kuesioner disusun dengan menggunakan skala likert yang berfungsi untuk memberikan informasi terkait dengan jawaban dari responden guna untuk mengumpulkan data mengenai analisis hambatan belajar siswa pada mata pelajaran informatika di MTsN 6 Agam. Hasil dari penelitian ini berupa analisis deskriptif data menunjukan bahwa N atau jumlah data variabel yang valid berjumlah 65, dengan nilai minium sebesar 14.00 dan nilai maksimum sebesar 46.00, yang diketahui nilai rata-rata sebesar 36.55, serta nilai standar deviasi sebesar 5.534, yang artinya nilai rata-rata lebih besar dari nilai standar sehingga penyimpangan data yang terjadi rendah.